Pharmacologic and surgical therapies for patients with Meniere’s disease: a protocol for a systematic review and meta-analysis - Ahmadzai, Nadera; Cheng, Wei; Wolfe, Dianna; Bonaparte, Jamie; Schramm, David; Fitzpatrick, Elizabeth; Lin, Vincent; Skidmore, Becky; Esmaeilisaraji, Leila; Kilty, Shaun; Hutton, Brian (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Hearing loss is one of the leading causes of disability in Canada and worldwide, with more than one million Canadians enduring a hearing-related disability. Meniere’s disease (MD) is a chronic condition of the inner ear, manifesting as a triad of disabling symptoms, including attacks of vertigo, fluctuating sensorineural hearing loss (SNHL), and tinnitus. Impacts on quality of life are severe, particularly with respect to restrictions in social participation and physical activity, fatigue, and reduced capacity to work. Anxiety and other psychological disorders may result from the restrictions imposed on life, the constant uncertainty of vertigo attacks, and fluctuating SNHL, with neuroses and depression affecting 40 to 60% of sufferers of intractable MD. There is a need to establish the benefits of previously studied interventions with greater certainty. The planned systematic review and meta-analyses/network meta-analyses (NMAs) will assess the relative effects of competing pharmacologic and surgical interventions for management of MD in adults. Methods An experienced medical information specialist in consultation with the review team will develop the electronic search strategies. We will search various databases including MEDLINE, Embase, and the Cochrane Library with no date or language restrictions for published literature, and key clinical trial registries for in-progress and completed trials. Screening of the literature will be performed by two reviewers independently using pre-specified eligibility criteria, and quality of the included studies will be assessed using the Cochrane Risk of Bias tool. We will resolve disagreements through consensus or third-party adjudication. When applicable, meta-analyses and NMAs will be pursued to compare interventions in terms of their effects on outcomes, including frequency and severity of vertigo, occurrence and intensity of tinnitus, changes in hearing and speech recognition, quality of life, and harms. Separate analyses exploring the effects of pharmacologic and surgical approaches will be performed. Discussion Our planned systematic review will provide informative evaluations of existing treatments for management of Meniere’s disease. The findings will inform practitioners as to the relative benefits and harms of the existing competing interventions for MD, offer optimal clinical treatment strategies, identify evidence gaps, and determine promising therapies for evaluation in future trials. Systematic review registration PROSPERO CRD42019119129